THE CONCEPT OF FEAR IN NIKOLAY RUDKOVSKI’S COMEDY „TO LIVE TO SEE THE OPENING NIGHT” AND IN THE TRANSLATIONS OF THE COMEDY INTO POLISH - Rusiecka, Natalia (Porównania, 2019)
This article attempts to analyze selected language exponents of the emotion of fear in the comedy “To Live to See the Opening Night”. This play was written in Russian by the contemporary Belarusian playwright Nikolay Rudkovski and translated into Polish by Bożena Majorczyk. Attention is drawn to the fact that, despite the similarity of “cultural scripts” and historical experiences, there are significant differences in the perception of the text between the recipients belonging to the Russian-speaking and the Polish-speaking cultural circle.